Penyebab Ketidaklengkapan Resume Medis Rawat Inap di RSU DR. H. Koesnadi Bondowoso - Ida Ayu Kurnia Dewi; Sabran; Atma Deharja; Demiawan Rachmatta Putro Mudiono (Indonesian Journal Publisher, 2024)
Total of 33% of 194 medical resume files experienced incomplete filling in the first quarter and second quarter of 2022. The purpose of this study was to analyze the factors causing incompleteness in inpatient medical resumes at Dr. H. Koesnadi Bondowoso Hospital. The research method applied was qualitative using data collection techniques through documentation, observation, and interviews. The research subjects consisted of the head of medical records, 3 doctors, 3 nurses, 3 admins, and 1 assembling medical recorder. The results of the study namely the lack of discipline of doctors in filling out medical resumes, the lack of knowledge of officers regarding filling completeness, there are doctors who have multiple job descriptions, there is no SOP for the completeness of filling out medical resumes, and there are still officers who do not follow the socialization of the SOP for the completeness of filling. The improvement efforts obtained are conducting socialization related to filling, cooperation between nurses and admins to remind doctors, doctors immediately fill out resumes after outpatient clinics, conducting training on filling completeness, limiting working hours and the number of patients handled by doctors, making SOPs for the completeness of medical resumes, and re-socializing SOPs.